توجهات الهدف لدى المتكونين دراسة ميدانية بمركز التكوين المهني و التمهين منصر عبد الله توقرت - بوعقه أسماء; درويش نجاة (جامعة الوادي - University of Eloued, 2025)
"ملخص الدراسة: هدفت الدراسة الحالية إلى التعرف على مستوى توجهات الهدف لدى المتكوّنين بمركز التكوين المهني والتمهين منصر عبد الله توقرت، في ضوء بعض المتغيرات. ولتحقيق أهداف الدراسة، تم الاعتماد على المنهج الوصفي القائم على الاستكشاف والمقارنة، واختيرت العينة بطريقة عشوائية طبقية، وتمت معالجة البيانات إحصائيا ببرنامج الحزمة الإحصائية(25spss,)، وقد أسفرت نتائج الدراسة على ما يأتي: 1- مستوى توجهات الهدف لدى المتكونين بمركز التكوين المهني والتمهين مرتفع. 2- توجد فروق دالة إحصائيا في مستوى توجهات الهدف لدى المتكونين باختلاف جنسهم لصالح الإناث. 3- لاتوجد فروق دالة إحصائيا في مستوى توجهات الهدف لدى المتكونين باختلاف وضعيتهم التكوينية. 4- لاتوجد فروق دالة إحصائيا في مستوى توجهات الهدف لدى المتكونين باختلاف نمط تكوينهم. وقد تم تفسير نتائج الدراسة بناء على الخلفية النظرية للدراسة، وبعض الملاحظات المستقاة من الميدان. ""Abstract: The current study aimed to identify the level of goal orientations among trainees at the Mansour Abdallah Touggourt Vocational Training and Professionalization Center, in light of certain variables. To achieve the study objectives, a descriptive approach based on exploration and comparison was adopted. The sample was selected randomly and stratified, and the data were statistically processed using the statistical package (SPSS,25). The study results yielded the following: 1-The level of goal orientations among trainees at the Vocational Training and Professionalization Center is high. 2-There are statistically significant differences in the level of goal orientations among trainees depending on their gender, in favor of females. 3-There are no statistically significant differences in the level of goal orientations among trainees depending on their training status. 4-There are no statistically significant differences in the level of goal orientations among trainees depending on their training style. The study results were interpreted based on the theoretical background of the study and someobservations drawn from the field. "
مذكرة ماستر قسم علم النفس وعلوم التربية تخصص إرشاد وتوجيه
Keywords: نمط التكوين; الوضعية التكوينية; المتكوّنين; توجهات الهدف; Goal orientations; trainees; Training style; Training status